Study on the effect of metronome-guided hand grip strength training with a ball in cancer patients with peripherally inserted central catheters (音乐节拍引导PICC置管肿瘤患者握球运动的作用研究) - TAN Yanmei (谭艳梅); ZHAO Huihan (赵慧函); HE Yu (何雨); LING Ying (凌瑛); YING Yanping (应燕萍) (Journal of International Translational Medicine Limited, 2022)
Objective To investigate the influence of different exercise guidance methods on compliance with hand grip strength training in cancer patients with peripherally inserted central catheters(PICC) placement, and to provide reference for the exercise guidance of patients with PICC placement. Methods Totally 100 patients with PICC placement were divided into intervention group and control group, with 50 cases in each group. In the control group, a hardcopy of guidance was sent to patients for guiding the hand grip strength training with a ball. In the intervention group, metronome-guided hand grip strength training was adopted. A 4-week intervention of training was conducted and patient compliance with training was evaluated during the follow-up. Results Before intervention, there was no significant difference in compliance with hand grip strength training between the two groups (P＞0. 05). The rate of compliance with hand grip strength training increased in both two groups after intervention(P＜0. 01), and rate of compliance in the intervention group was higher than that in the control group(P＜0. 05). Conclusion The metronome-guided hand grip strength training with a ball could effectively improve the compliance of cancer patients with PICC catheterization. It could provide reference for the exercise guidance of patients with PICC catheterization. (目的 探讨不同运动指导方式对经外周静脉置入中心静脉导管(PICC)置管肿瘤患者握球运动依从性影响, 为临床PICC置管患者运动指导提供参考。方法 选取某三级甲等医院血液内科收治PICC置管患者100例为观察对象, 分为干预组和对照组, 各50例。干预组接受音乐节拍指导握球运动, 对照组接受纸质版图文运动指导, 干预时间为4周。两组患者干预前后均使用握球运动依从性量表评价握球运动依从性。结果 干预前, 两组患者握球运动依从性差异无统计学意义(P＞0. 05)。干预后, 两组患者握球运动依从性高于干预前(P＜0. 01), 且干预组患者握球运动依从性高于对照组, 差异具有统计学意义(P＜0. 05)。结论 音乐节拍引导PICC置管肿瘤患者握球运动能显著提高其运动依从性, 为临床PICC置管患者运动指导提供参考。)